A mechanical model for the shear capacity of slender reinforced concrete members without shear reinforcement. (15th September 2020) - Tran, Ngoc Linh
Highlights: A general shear model for RC members without shear reinforcement is introduced. The proposed approach consistently applies laws of mechanics with realistic physical quantities. Fracture energy, crack width and crack spacing are taken into account in detail. Advances in research on material and cracking behaviour will automatically improve the model accuracy. Abstract: A new approach to shear capacity of slender concrete beams without shear reinforcement based on principles of structural mechanics is presented. It is assumed that the shear capacity corresponds to a failure that takes place at the neutral axis when the principal tensile stress of concrete reaches the effective concrete tensile strength, resulting in a sudden crack connecting to the critical shear crack tip. Realistic values of material and structural properties such as concrete tensile strength, elastic modulus, fracture energy, crack width and crack spacing are analysed and directly taken into account in the new model. In contrast to many existing shear models, the size effect is considered naturally through the fracture energy of concrete together with the crack spacing. The accuracy of the proposed method has been verified by comparing model predictions with experimental results of different concrete members. The new shear model shows a consistent and higher accuracy of shear capacity prediction than most existing shear models including those in current codes. The validation results and other aspects of the shear model are discussed, leading to some conclusions on the new shear model and its applications.